The Influence of Teacher Competency, Teacher Commitment, and Workload on Teacher Performance - NIngsih, Luh Kartika; Sugiantari, Komang Linda; Widnyani, Ni Made (Jurnal Manajemen, 2024)
This study aims to determine the effect of teacher competence, teacher commitment, and workload on teacher performance at SMP Negeri 1 Banjar. The population and research sample were 59 teachers. The results of this study indicate that the influence of teacher competence has an effect on teacher performance at SMP Negeri 1 Banjar, with competence possessed by teachers at work being able to help them improve their work results by sharing their knowledge and sharing it among fellow teachers in an effort to achieve goals desired learning. Teacher commitment affects teacher performance at SMP Negeri 1 Banjar with the length of service the teacher has to teach at agencies, a high commitment to agencies, and a feeling of comfort in carrying out work can help these teachers improve their performance. The effect of workload on teacher performance at Banjar 1 Public Middle School is evidenced by the process of assigning teacher workloads, which were given at the beginning of the school year meeting it was determined that at least the teacher had to teach 24 hours a week, with the workload given to the teachers concerned and the responsibilities charged by the teacher can improve the performance it has. The effect of teacher competence, teacher commitment and workload on teacher performance is 78.2%, while other variables influence another 21.8%